2016
DOI: 10.1186/s40878-016-0023-1
|View full text |Cite
|
Sign up to set email alerts
|

Eurocity London: a qualitative comparison of graduate migration from Germany, Italy and Latvia

Abstract: This paper compares the motivations and characteristics of the recent migration to London of young-adult graduates from Germany, Italy and Latvia. Conceptually the paper links three domains: the theory of core-periphery structures within Europe; the notion of London as both a global city and a 'Eurocity'; and the trope of 'crisis'. The dataset analysed consists of 95 in-depth biographical interviews and the paper's main objective is to tease out the narrative similarities and differences between the three grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 31 publications
5
63
0
3
Order By: Relevance
“…Part of the answer can be found in some recent studies on Italian graduates (King, R. and Conti, F. 2013;King, R. et al 2014King, R. et al , 2016b) that point out how young Italians are fleeing from something intangible as well as from economic stresses and employment crisis. They are running away from a system they call "gerontocratic", "clientelist", "corrupt" and "not merit-based", where finding a job requires "recommendations" and networks of personal connections.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Part of the answer can be found in some recent studies on Italian graduates (King, R. and Conti, F. 2013;King, R. et al 2014King, R. et al , 2016b) that point out how young Italians are fleeing from something intangible as well as from economic stresses and employment crisis. They are running away from a system they call "gerontocratic", "clientelist", "corrupt" and "not merit-based", where finding a job requires "recommendations" and networks of personal connections.…”
Section: Resultsmentioning
confidence: 99%
“…A high percentage of Italians moving to Germany (especially women) were under the age of 25 (Haug, S. 2015). King, R. et al (2016b), in their analysis of new flows of young people -Germans, Italians and Latvians -in London, draw attention to characteristics including: (i) the renewed importance of the contrast between developed and less-developed economies in the world and in Europe, (ii) the attractiveness of London as a Eurocity (Favell, A. 2008) and a global city (Sassen, S. 2001), and (iii) the economic crisis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30][31][32][33][34][35][36][37][38]. Responding to this inviting opening, the present article is based on data collated via participatory ethnography, including semi-structured participant interviews, between October 2014 and January 2016 as part of the ongoing "Transnationalizing Modern Languages" project ("TML").…”
Section: Introductionmentioning
confidence: 99%
“…King et al (2014) take this argument further by arguing that the 'lure of London' makes it distinctive to international students relative to all other English locations, thus opening the interesting prospect of researching glocalisation effects on student flows arising from the geography of globalisation in relation to global cities and their positioning in the differentiation of higher education. Work on international students found that the image of London dominated perceptions of study in England, with universities outside London being defined largely in terms of their proximity to the UK's leading global city (Beech 2014).…”
Section: "Yeah -Well To Be Honest With You It Was Definitely That Tmentioning
confidence: 99%